1990
DOI: 10.1021/bi00462a001
|View full text |Cite
|
Sign up to set email alerts
|

Distinction between the two basic mechanisms of cation transport in the cardiac sodium-calcium exchange system

Abstract: In order to distinguish between the Ping-Pong and sequential mechanisms of cation transport in the cardiac Na(+)-Ca2+ exchange system, the initial rates of the Nai-dependent 45Ca uptake (t = 1 s) were measured in reconstituted proteoliposomes, loaded with a Ca chelator. Under "zero-trans" conditions ([Na]o = [Ca]i = 0) at a fixed [Na]i = 10-160 mM with varying [45Ca]o = 2.5-122 microM for each [Na]i, the Km and Vmax values increased from 7.7 to 33.5 microM and from 2.3 to 9.0 nmol.mg-1.s-1, respectively. The V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(45 citation statements)
references
References 32 publications
1
44
0
Order By: Relevance
“…The current amplitude declines at all membrane potentials during Ca2" application, but the decline seems to be more significant at negative membrane potentials. This tendency is consistent with I-V relation changes of the outward exchange current in giant membrane patches in response to an increase of the cytoplasmic Ca2+ concentration or a decrease of cytoplasmic Na+ concentration (Matsuoka & Hilgemann, 1992 (Khananshvili, 1990;Li & Kimura, 1990Hilgemann, Nicoll & Philipson, 1991;Niggli & Lederer, 1991). A consecutive model with one transition to an inactive state (Scheme 1), taking place from the three Na+-loaded exchanger conformation with cytoplasmic orientation of binding sites, described well many experimental results on the inactivation of exchange current in giant patches (Hilgemann et al 1992b).…”
Section: Resultssupporting
confidence: 85%
“…The current amplitude declines at all membrane potentials during Ca2" application, but the decline seems to be more significant at negative membrane potentials. This tendency is consistent with I-V relation changes of the outward exchange current in giant membrane patches in response to an increase of the cytoplasmic Ca2+ concentration or a decrease of cytoplasmic Na+ concentration (Matsuoka & Hilgemann, 1992 (Khananshvili, 1990;Li & Kimura, 1990Hilgemann, Nicoll & Philipson, 1991;Niggli & Lederer, 1991). A consecutive model with one transition to an inactive state (Scheme 1), taking place from the three Na+-loaded exchanger conformation with cytoplasmic orientation of binding sites, described well many experimental results on the inactivation of exchange current in giant patches (Hilgemann et al 1992b).…”
Section: Resultssupporting
confidence: 85%
“…If common binding sites, translocation pathways, or both are used, does every substrate use all of the same features of the site or pathway to the same extent, or is there variability among substrates? And is a single translocation pathway used for the efflux substrates and coupling ions in an alternating, ping-pong type of mechanism, as is found for many antiporters (8,16,21,29,40,44), or are the efflux substrates and coupling ions translocated simultaneously through distinct translocation pathways, as in some other antiporters (6,40)? Complete resolution of these major questions will require high-resolution structural data in addition to more detailed studies of binding and transport kinetics and more extensive mutagenesis studies in combination with approaches to provide additional structural information.…”
Section: Discussionmentioning
confidence: 99%
“…2). Kinetic studies using reconstituted proteoliposomes (61,62) and an electrophysiological technique (60,63,64) showed that the apparent affinity of the exchanger for one ion increased as the concentration of the trans ion decreased, indicating a characteristic property of a con secutive reaction cycle. Ion binding sites can be assumed to have a net charge of 2.…”
Section: Mechanismmentioning
confidence: 99%